2007
DOI: 10.1245/s10434-007-9659-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome after Selective Treatment of Patients Diagnosed with Ductal Carcinoma In Situ of the Breast

Abstract: BCT of DCIS bears the risk of residual disease progressing into invasive local recurrence and distant metastasis. A re-excision or mastectomy is therefore desired in all patients with unclear margins. Mastectomy treatment is associated with optimal local control and might be considered for patients younger than 40 years who are at high risk of local recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 20 publications
4
56
0
3
Order By: Relevance
“…More important, the risk of LRR for patients with close margins was lower than the risk of development of contralateral breast cancer (6.4 %). The rate of contralateral breast cancer development is essentially the same as the rate reported by Meijnen et al 9 for patients with DCIS treated with mastectomy: 6.5 % over 8 years. Further, Kim et al 21 reported that 90 % of patients treated with mastectomy for DCIS who developed a LRR were successfully treated with excision and radiotherapy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…More important, the risk of LRR for patients with close margins was lower than the risk of development of contralateral breast cancer (6.4 %). The rate of contralateral breast cancer development is essentially the same as the rate reported by Meijnen et al 9 for patients with DCIS treated with mastectomy: 6.5 % over 8 years. Further, Kim et al 21 reported that 90 % of patients treated with mastectomy for DCIS who developed a LRR were successfully treated with excision and radiotherapy.…”
Section: Discussionsupporting
confidence: 81%
“…[3][4][5] The local regional recurrence (LRR) rate for DCIS treated with mastectomy is not zero and is reported to be 0.8-3.3 %. [6][7][8][9][10] Several studies have evaluated potential predictors of LRR after mastectomy for DCIS in an attempt to improve the already low rates of LRR. [11][12][13][14][15][16] One of these potential predictors is margin status.…”
mentioning
confidence: 99%
“…In the United States, the overall mastectomy rate decreased from 43% in 1992 to 37% in 1995 and 28% in 1999 Baxter et al, 2004;Mokbel and Cutuli, 2006). However, this rate was much higher (58%) in a large series from the Netherlands Cancer Institute (Meijnen et al, 2008). Tumour Table 3 Influence of tumour size, nuclear grade, necrosis and age on treatment modality (number and percent patients) (Fisher et al, 2001;Solin et al, 2001;Cutuli et al, 2002;Fourquet et al, 2002;Vicini and Recht, 2002;Bijker et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…(7) It was found the mean size of DCIS of 1.4 to 2.7 cm, (4) 3.5 cm (8) and 3.7 cm (9) (measured pathologically), 1 to 1.5cm (10) and 2.56 cm. (11) Our study reports a tumor which size is greater than two times of the majority of the descriptions.…”
Section: Discussionmentioning
confidence: 98%
“…(1) The main cancer to affect Brazilian women is non-melanoma skin cancer (71.000 new cases), followed in order of frequency by malignant neoplasms of the breast (53.000), cervix uteri (18.000), colon/rectum (16.000) and lung (10.000). (1) Clinical presentation of pure Ductal Carcinoma in Situ (DCIS) is often described as extension small tumors (4)(5)(6)(7)(8)(9)(10)(11) detected mainly by mammography. Recognizing this type of tumor may manifest as palpable lesion, it is necessary to know and to apply methods that allow diagnosis early: self-breast examination, and clinical examination by a trained team.…”
Section: Introductionmentioning
confidence: 99%